Suspects. [videorecording (DVD)] Series three & four - Molony, Damien; Ashitey, Clare-Hope, 1987-; Ripley, Fay, 1966- (Acorn Media, 2016)
"Detectives Martha Bellamy (Fay Ripley, Cold Feet), Jack Weston (Damien Molony, Being Human), and Charlie Steele (Clare-Hope Ashitey, Children of Men) are back to solve a series of all-new mysteries in contemporary London. From an arson attack that leaves a teenager fighting for his life to a copycat murder that could be the work of a serial killer, Martha and her team work tirelessly to expose the truth behind each crime. Filmed from an eyewitness perspective with improvised dialogue, this one-of-a-kind procedural delivers an immersive, authentic look at police investigations, hailed as “a fresh take on the usual cop show”--Container.